Desafios da Educação Infantil em tempos pandêmicos: afetividade e acolhimento - Moda, Julia Niero (Universidade Federal de São Carlos, 2024)
The present undergraduate thesis aims to understand the issue of affection and reception of children in Early Childhood Education, as well as the challenges faced by this stage of education to exercise them during the pandemic period. In order to carry out this work, were carried out bibliographic and documentary research, with a qualitative approach. Thereby, besides books, research, articles and academic texts, were also used news and television reports related to confront of the covid-19 pandemic by the Early Childhood Education school community. The text begins with a historical resumption of Early Childhood Education in Brazil and the rights guaranteed to children over time. the results obtained through the analysis of reports, related to the historical reference, point out that the remote proposals taken by schools as a measure to face the isolation during the pandemic, disrespected the guarantee of children's rights and ignored the specificities of Early Childhood Education.
The challenges of Early Childhood Education in pandemic times: affection and reception
Keywords: Educação Infantil; Pandemia; Desafios; Early Childhood; Pandemic; Challenges; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO